Implementation of Discovery Learning Assisted by Pythagorean Puzzle to Improve Mathematical Problem-Solving Ability - Mutmainah, Fatikhatun; Rozaq, Hasri Akbar Awal (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
A Mathematical problem-solving ability is the ability of students to solve a mathematical problem. External factors that affect mathematical problem-solving ability are the methods and learning media used. Researchers apply the discovery method assisted by learning media which is one of the alternatives to improve mathematical problem-solving ability, namely the discovery learning model assisted by the Pythagorean Puzzle. This study aims to determine the effectiveness of discovery learning assisted by the Pythagorean Puzzle in improving the mathematical problem-solving ability of class VIII students of MTs Muhammadiyah 01 Purbalingga. This research is quasi-experiment research with a quantitative approach. The population in this study were students of class VIII MTs Muhammadiyah 01 Purbalingga which amounted to 163 students. The samples of this study were class VIII C which amounted to 22 students as the Experiment class and class VIII D which amounted to 22 students as the Control class. Data collection in this study used instruments in the form of observations and tests of mathematical problem-solving skills. Based on the analysis obtained, discovery learning assisted by Pythagorean Puzzle was implemented very well. The results of data analysis using the T-test, and post-test comparison test obtained sig (2-tailled) of 0.000 < 0.05, which means that there is a difference in the average experimental class and control class. So, it can be concluded that the implementation of discovery learning assisted by the Pythagorean Puzzle is effective in improving the mathematical problem-solving skills of class VIII students of MTs Muhammadiyah 01 Purbalingga.